A Tenodesis-Induced-Grip exoskeleton robot (TIGER) for assisting upper extremity functions in stroke patients: a randomized control study. Issue 23 (6th November 2022) - Hsu, Hsiu-Yun; Yang, Kang-Chin; Yeh, Chien-Hsien; Lin, Yu-Ching; Lin, Keng-Ren; Su, Fong-Chin; Kuo, Li-Chieh
Abstract: Purpose: This study was aimed toward developing a lightweight assisting tenodesis-induced-grip exoskeleton robot (TIGER) and to examine the performance of the TIGER in stroke patients with hemiplegia. Methods: This was a single-blinded, randomized control trial with pre-treatment, immediate post-treatment, and 12-week follow-up assessments. Thirty-four stroke patients were recruited and randomized to either an experimental or control group, where each participant in both groups underwent 40 min of training. In addition to a 20-min bout of regular task-specific motor training, each participant in the experimental group received 20 min of TIGER training, and the controls received 20 min of traditional occupational therapy in each treatment session. Primary outcomes based on the Fugl-Meyer Motor Assessment of Upper Extremity (FMA-UE) were recorded. Results: Thirty-two patients (94.1%) completed the study: 17 and 15 patients in the experimental and control groups, respectively. Significant beneficial effects were found on the total score (ANCOVA, p = 0.006 ), the wrist score (ANCOVA, p = 0.037 ), and the hand score (ANCOVA, p = 0.006 ) for the FMA-UE in the immediate post-treatment assessment of the participants receiving the TIGER training. Conclusion: The TIGER has beneficial effects on remediating upper limb impairments in chronic stroke patients. Clinical trial registration: ClinicalTrials.gov; identifier NCT03713476 Implications for rehabilitation: Based on use-dependent plasticity concepts, robot training with the more distal segments of the upper extremities has a beneficial effect in patients with chronic stroke. A novel lightweight assisting tenodesis-induced-grip exoskeleton robot (TIGER) system using a mechanism involving musculotendinous coordination of the wrist and hand was proposed in this study. Between-group differences in changes in the upper limb motor performance were observed in the experimental group as compared to patients in the control group. For patients with chronic stroke, receiving 20 min of TIGER training in conjunction with 20 min of task-specific motor training led to clinically important changes in motor control and functioning of the affected upper limb.